Qualitative analysis and chemical characterization of oil derived from unripe fresh fruit bunches / Syaidatul Aishah Johari - Johari, Syaidatul Aishah (Faculty of Plantation and Agrotechnology, 2017)
Malaysia is currently the second producer in of palm oil in the world. One of the problems in the plantation industry is the in efficient harvesting of ripe FFB, where harvester may accidentally harvest unripe FFB. It will create environmental was disposal and cause losses of oil to the industry. A preliminary study was conducted at Sime Darby Kempas Palm Oil Mill to study the quality and chemical characteristic of oil extracted from unripe FFB of the differences sizes and to compare the oil quality of unripe FFB with the ripe FFB. The parameters used to determine the quality of oil were Free Fatty Acid (FFA), moisture content, impurities content and Deterioration of Bleachability Index (DOBI). The results showed that, there was no significant different of the quality of oil extracted from the unripe FFB of the different sizes. The quality unripe FFB oil was also in the range of good quality according to MS 814, where the FFA (0.5%-0.7%), moisture (0.13%-0.18%), impurities (0.002%-0.008%) and DOBI (2.80-3.40). Meanwhile for comparison the quality oil for Ripe and Unripe FFB, the results showed that FFA and impurities of ripe FFB was higher than unripe FFB. Where for moisture and DOBI unripe FFB is higher than ripe FFB. This study concludes the unripe FFB can be processed because it has in range in good quality but oil percentage was quite low. In conclusion, this study will give many benefit where is to generate profit, avoid losses and avoid Unripe FFB become not useful waste that will lead to pollution for environment. Further research can be done by turning this rejected fruit into beneficial product because this study has proven the quality oil extracted from unripe FFB has in range good quality.